REPRESENTASI BUDAYA DALAM VIDEO DOKUMENTER SEBAGAI STRATEGI BRANDING DESTINASI: STUDI KASUS DESA ABAFALA, TIMOR LESTE - Zainal Abidin Achmad; Egidia Putri Teresia Sembiring Maha; Michelle Librianora Simangasing; Mahendra Rizky Putra Pratama; Dedin Finatsiyatull Rosida; Crystia Aji Putra (PETA - Jurnal Pesona Pariwisata, 2026)
This study aims to analyze how cultural representation in documentary videos plays a role in the destination branding strategy of Abafala Village, Timor-Leste. The study employed a qualitative method with a case study approach, focusing on the analysis of the documentary's visual narrative as the primary object. Data were collected through in-depth interviews with community leaders, observations of cultural practices, and analysis of the documentary's audiovisual content. The analysis was conducted thematically to identify elements of cultural representation and the construction of the destination image. The results show that the documentary serves as a representational medium that constructs destination identity through visualizations of landscapes, traditional architecture, and community cultural practices. This representation not only reflects social reality but also constructs symbolic meanings that strengthen the village's authentic image. Furthermore, distribution through social media broadens the reach of representation and encourages audience engagement as part of the destination image formation process. This study confirms that documentary videos function not merely as promotional media but as a communication mechanism that integrates narratives, symbols, and experiences in shaping cultural identity-based destination branding.